A novel geriatric assessment tool that predicts postoperative complications in older adults with cancer. Issue 5 (June 2020) - Pollock, YaoYao; Chan, Chiao-Li; Hall, Karen; Englesbe, Michael; Diehl, Kathleen M.; Min, Lillian
Abstract: Introduction: Comprehensive geriatric assessment prior to oncologic surgery can help predict surgical outcomes. We tested whether an abbreviated geriatric assessment tool, the Vulnerable Elderly Surgical Pathways and outcomes Assessment (VESPA), would predict post-operative complications among older adults undergoing oncologic surgery. Method: From 2008 to 2011, geriatric assessments were completed using the VESPA tool for patients age ≥ 70 seen in a pre-operative clinic. The VESPA assessed functional status, mood, cognition, and mobility, and can be completed in <10 min. We selected the subset of patients who underwent oncologic surgery and evaluated the VESPA's ability to predict post-operative surgical complications, geriatric complications (e.g., delirium), length of stay, and geriatric post-discharge needs (e.g., new functional dependence). Results: A total of 476 patients who underwent oncologic surgery received the assessment using VESPA. Compared to patients with low VESPA scores (<9), patients with high VESPA scores (≥9) had longer length of stay (mean 6.6 vs. 2.0 days; p < .001), more geriatric complications (39.5% vs. 5.7%; p < .001), more surgical complications (29.5% vs. 11.8%; p < .001), and more likely to have post discharge needs (76.0% vs. 31.7%; p < .001). Using logistic regression, each additional point on the VESPA scale was also associated with increased probability of geriatric complications (OR = 1.3; 95% CI = 1.2–1.4), surgical complications (OR = 1.2; 95% CI = 1.1–1.2), and geriatric post-discharge needs (OR = 1.3; 95% CI = 1.2–1.3). Conclusion: The VESPA identifies older patients with cancer who are at risk for postoperative surgical and geriatric complications as well as functional needs at hospital discharge.